Determinan Pembelian Kompulsif pada Mahasiswa Pengguna Buy Now Pay Later - Rina Sari Qurniawati; Dhandy Rachmat Andreyan; Yulfan Arif Nurohman (Peneliti.net, 2023)
Students prefer to use paylater payments rather than using bank credit loans because there is no need for them to provide guarantees. With the development of paylater payments in Indonesia since the pandemic, this has led to compulsive buying behavior. For this reason, this research has an urgency to be carried out so that people have control over their behavior. In testing the hypothesis using multiple linear regression using SPSS version 25. after testing the validity and reliability using 125 samples, it is continued with multiple linear regression tests. The results of this study are the pain of paying and the ease of payment methods that prove to affect compulsive buying. while financial literacy is not proven to have an effect on compulsive buying